A new elasmosaurid from the upper Maastrichtian López de Bertodano Formation: new data on weddellonectian diversity - O'gorman, Jose Patricio; Panzeri, Karen Magalí; Fernández, Marta Susana; Santillana, Sergio; Moly, Juan J.; Reguero, Marcelo Alfredo (Alcheringa: An Australasian Journal of Palaeontology)
Elasmosaurids are one of the most frequently recorded marine reptiles from the Weddellian Province (Patagonia, Western Antarctica and New Zealand). Improvements in our knowledge of elasmosaurid diversity have been problematic because of their conservative postcranial morphology. However, recent studies have helped to improved our understanding of the diversity of this group. Here, a new elasmosaurid specimen from the upper Maatrichtian horizons of the López de Bertodano Formation, Antarctica, MLP 14-I-20-16, is described. MLP 14-I-20-16 is one of the youngest non-aristonectine weddellonectian elasmosaurids from Antarctica. We confirm the coexistence of aristonectine and non-aristonectine elasmosaurids in Antarctica until the end of the Cretaceous. MLP 14-I-20-16 shows distinctive short and broad posterior cervical vertebrae, a feature only shared among the weddellonectian elasmosaurids by the Maastrichtian Morenosaurus stocki, although the same vertebral proportions are also recorded for the giant Cenomanian elasmosaurids Thalassomedon haningtoni. Comparison between MLP 14-I-20-16 and other elasmosaurids from the Maastrichtian of Antarctica indicates that at least two different non-aristonectine elasmosaurids were present in Antarctica during the late Maastrichtian. Fil: O'gorman, Jose Patricio. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: Panzeri, Karen Magalí. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: Fernández, Marta Susana. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: Santillana, Sergio. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. ...